Վանականներին վերաբերող կանոնները Հայոց Եկեղեցում - Ծատուրեան, Անանիա աբղյ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена канонам регулирующим монастырский уклад жизни последователей Армянской Апостольской церкви. В армянской действительности имел широкое распространение монастырский устав написанный Св. Василием Великим. Подобные предписания присутствуют в различных группах канонов, вошедших в «Армянскую книгу канонов», а также в различных поучениях и речах многих авторов. В статье подробно рассмотрены каноны, относящиеся к трем монашеским обетам — целомудрию, нестяжанию и послушанию, а так- же каноны определяющие духовные и бытовые стороны жизни монахов. This article deals with the canons regulating the monastic lifestyle of the Armenian Apostolic Church. The Monastic Statute authored by St. Basil the Great was especially widely used in the Armenian reality. Similar rules are also present in various groups of canons found in the “Armenian Book of Canons,” as well as in individual exhortations and discourses by various authors. The article discusses in detail the canons concerning three monastic vows: vows of virginity, abstinence and obedience, as well as the rules related to the monks’ prayer, ritual life and other household realities.
Keywords: Կրօնագիտութիւն